Competitive Advantage Based on the Resources of E-Commerce Platforms in Vietnam - Huong, Nguyen Thi Thu; Dung, Nguyen Thuy (Archives of Business Research, 2023)
With the growing socio-economic environment, the industrial revolution 4.0 appears in all areas of life. In Vietnam, buying and selling on e-commerce platforms is growing. This creates increasingly fierce competition among businesses in this industry. The study aims to explore the competitive strategies of e-commerce platforms in Vietnam today. The article uses the expert interview method combined with the document research method to analyze how to create a competitive advantage based on the resources of e-commerce platforms in Vietnam, such as Shopee, TikTok Shop, Lazada, Tiki, and Sendo. Research shows that successful e-commerce platforms all try to focus on creating advantages from valuable, rare, inimitable, and non-substitutable resources, in which human resources, finance, and customer data play an essential role. From the research results, the article makes recommendations for the remaining enterprises in the industry to gain a sustainable competitive advantage in their own "home turf."